Compensation of the magnetic force imaging by scanning directions. (November 2017) - Liu, Jinyun; Yu, Miao; Qu, Yingmin; Zhang, Wenxiao; Fan, Yinxue; Song, Zhengxun; Qiu, Renxi; Li, Dayou; Wang, Zuobin
Highlights: Three different scanning directions with the angles 0°, 45° and 90° were studied. A method for the distortion compensation was proposed to reduce the errors. The distortion structures were corrected with the proposed compensation method. The effect of scanning directions on the MFM imaging was significantly reduced. Abstract: It was found that the results of magnetic force microscope (MFM) imaging were different with the probe scanning directions. This paper studied the effect of scanning directions on the MFM imaging, and a method for the distortion compensation was proposed to reduce the errors. In the study, three different scanning directions with the angles of 0°, 45° and 90° were used to measure the magnetic domain structures distributions of magnetic sample. The experimental results have shown that the scanning direction parallel to the magnetic domain structure will cause a minimum phase shift difference and lead to a structure distortion. A method for compensating the distortions was proposed. With this method, the distorted structures were corrected and the effect of scanning directions on the MFM imaging was significantly reduced. This work provides a way for the acquisition of the correct images of magnetic structures using an MFM and the improvement of imaging quality in a wide range of MFM applications.